Transformation of Marketing Strategy in Decision Making in the Era of Globalization: Case Analysis of PT.Indofood Sukses Makmur, Tbk - Ardiansyah, Nisa; Aurellia, Raihana Zahra; Anatasya, Wahyu; Carolline P.S, Petra; Hidayat N, Rusdi; Kusumasari , Indah Respati (Journal of Advances in Accounting, Economics, and Management, 2024)
Globalization and the development of digital technology have created both challenges and opportunities for multinational companies, including PT Indofood Sukses Makmur Tbk. This research aims to examine how Indofood implements an adaptive marketing strategy in the face of the challenges of globalization and accelerated digitalization. Using the literature study method, this research explores the key factors that contribute to the success of Indofood's marketing strategy. The findings show that Indofood's success is underpinned by the implementation of an integrated glocalization strategy, product innovation that meets the needs of the local market, utilization of digital technologies such as big data and e-commerce, and flexible and responsive human resource management. This strategic approach helps Indofood maintain its global competitiveness while still meeting the needs of domestic consumers. The study also highlights the importance of integrating global and local strategies, continuous innovation, and the company's ability to adapt to market changes. Through the case study of Indofood, this research offers conceptual guidance for manufacturing companies in Indonesia looking to develop marketing strategies in the digital age.